PERSPEKTIF EKONOMI DAN BISNIS ISLAM MENGENAI PENGARUH INDEKS PEMBANGUNAN MANUSIA, TINGKAT KEMISKINAN, DAN BELANJA MODAL TERHADAP PENGANGGURAN TERBUKA DI JAWA BARAT TAHUN 2002-2021 - Puloh; Rifai, Muhamad; Faiz, Marcelino; Putri, Hani Cahyani (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This study aims to show the impact of the Human Development Index, poverty, capital expenditure on the level of open response in West Java Province in 2002-2021. Data collection uses secondary data on the Human Development Index, poverty rate and spending capital in West Java Province obtained from the Badan Pusat Statistik in the form of time series data from 2002 to 2021. The analytical method used in this study is the multiple regression analysis method which consists of more than one independent variable, processed using the SPSS 26 application, produces a regression equation for IPM = - 0.019;MSK = 0.793;BM = - 0.034 . The results of this study indicate that the IPM variable has a significant negative effect on the level of open stimulation. While the Capital Expenditure variable has a negative and insignificant effect on the level of open response.